Analisis Administrasi Bencana Berbasis Data Korban: Studi Banjir Bandang Sumatera Barat - Wahyuni, Tiara (Department of Public Administration, Muhammadiyah University of Makassar, 2026)
The flash floods in West Sumatra caused significant impacts on public safety, environmental conditions, and social stability, creating serious challenges for local governments in disaster management. This study aims to analyze disaster administration through a casualty-based approach by examining the response capacity of local governments in handling flash flood disasters across six districts and municipalities in West Sumatra. This research employed a descriptive qualitative–quantitative method using comparative analysis of casualty data obtained from the Health Crisis Center of the Indonesian Ministry of Health. The recorded data show that 9,241 residents were affected, including 60 deaths, 13 victims with severe or minor injuries, 9,524 outpatients, and 4,522 displaced people. The findings indicate significant differences in disaster impacts among regions. Tanah Datar recorded the highest number of affected residents and outpatient injuries, while Agam had the highest number of fatalities. Padang City, despite having fewer affected residents, still recorded deaths, showing that disaster severity is influenced not only by population exposure but also by preparedness, response speed, and institutional coordination. The study concludes that effective disaster management depends on institutional readiness, strong inter-agency coordination, efficient early warning systems, and adequate emergency health services. Strengthening local government capacity and community preparedness is essential to reduce casualties and improve long-term disaster resilience.